2014
DOI: 10.1007/s00339-014-8506-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of laser wavelength on the ablation rate of carbon

Abstract: The ablation of graphite is studied as a function of laser fluence for 355, 532 and 1,064 nm wavelength generated by a nanosecond Nd:YAG laser. It has been found that in the case of lower wavelengths, the transition from the thermal ablation to the phase explosion takes place at lower laser fluences. The change of crater shape due to the effect of deep drilling in the proximity of the phase explosion threshold was observed. The calculations of plasma radiation flux to the target surface were made, and the cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 24 publications
3
35
1
Order By: Relevance
“…This ablation threshold is higher than the value found by Zhang et al [21], but we also worked at a longer wavelength, namely 1030 nm versus 800 nm. This seems to be in line with earlier wavelength dependence studies [22]. The smallest measured diameter of the ablated spot was 8 μm, which in combination with highprecision alignment stages enables patterning of graphene with micron-scale resolution.…”
Section: Femtosecond Laser Ablationsupporting
confidence: 90%
“…This ablation threshold is higher than the value found by Zhang et al [21], but we also worked at a longer wavelength, namely 1030 nm versus 800 nm. This seems to be in line with earlier wavelength dependence studies [22]. The smallest measured diameter of the ablated spot was 8 μm, which in combination with highprecision alignment stages enables patterning of graphene with micron-scale resolution.…”
Section: Femtosecond Laser Ablationsupporting
confidence: 90%
“…The explanation of ultradeep drilling was supported recently by comprehensive experimental and theoretical studies performed by Hoffman et al [51] using 355, 532 and 1064 nm wavelengths generated by a nanosecond Nd:YAG laser. It was found that at lowest wavelength, the transition from thermal ablation to phase explosion takes place at lower laser fluences.…”
Section: Plasma-assisted Ultradeep Ablationmentioning
confidence: 86%
“…While the role of the recoil pressure of plasma plumes under PLA is extensively discussed in the literature (see, e.g., [46][47][48][49]), detailed analysis of the plasma reradiation effects on the ablation process is still lacking. Only recently comprehensive experimental and theoretical studies were performed, which have shown that the radiating laser-ablation plasma can dramatically influence the ablation dynamics, leading to the formation of ultradeep craters [50][51][52]. On the example of graphite, it was clearly demonstrated that ultradeep crater formation can only be explained based on the concept of ablation plasma absorption and reradiation [50,51].…”
Section: Plasma-assisted Ultradeep Ablationmentioning
confidence: 99%
See 1 more Smart Citation
“…This material is vaporized from the target, forms a plasma plume, and subsequently deposits as a thin film on a substrate. The ejected species expand into the surrounding vacuum (or ambient gas) in the form of a plume containing many energetic species including atoms, molecules, electrons and ions [26,27] prior to deposition on the substrate. After deposition of the evaporated material on the surface of the substrate, its re-synthesis occurs.…”
Section: Introductionmentioning
confidence: 99%